Effects of Dynamic Topography on the Cenozoic Carbonate Compensation Depth. (2nd April 2018) - Campbell, Siobhan M.; Moucha, Robert; Derry, Louis A.; Raymo, Maureen E.
Abstract: Reconstructions of the carbonate compensation depth (CCD) in the past have been used to inform hypotheses about the nature of weathering, tectonics, climate change, and the major ion content of the world's oceans over the Cenozoic. These reconstructions are sensitive to uncertainties in the input data, in particular, the paleodepth estimates of sediment cores. Here we propose that a significant, previously unconsidered contributor to uncertainties in paleodepth estimates is from dynamic topography produced by radial stresses exerted on the Earth's surface by the convecting mantle; these stresses can warp the ocean floor by hundreds of meters over broad regions and also vary significantly over millions of years. We present new reconstructions of the equatorial Pacific and Indian Ocean CCDs over the last 30 and 23 Myr, respectively, which demonstrate an overall deepening trend since the Miocene, and illustrate the possible effect of long‐term changes in dynamic topography on these reconstructions. Key Points: Reconstructions of the carbonate compensation depth require that changes in dynamic topography be considered The carbonate compensation depths of both the Indian and Pacific Oceans reflect an overall deepening trend since the Miocene